Mutagenic impact of picric acid on chloroplast genome and a selection of biological attributes of Brassica napus L. (Brassicaceae) - Ishtiaq Ahmad; Barkat Ullah; Zahir Muhammad; Dikhnah Alshehri; Muhammad Nauman Khan; Alevcan Kaplan; Majid Iqbal; Laila A. Al-Shuraym; Uthman Balgith Algopishi; Sadeq K. Alhag; Meshari A. Alsuwat; Diriba Dereje Olana; et al. (BMC Genomics)
Abstract The present study was conducted to investigate the possible mutagenic effects of picric acid on the chloroplast genome and certain biological properties of Brassica napus L. under field conditions. The experimental design for this study was a randomized complete block trial, based on 3 factors (dose, duration of priming, and three oilseed rape (cultivars). The seeds of oilseed rape cultivars (Abasin- 95, Dur e Nifa, and Nifa Gold) were exposed to five doses (0 mM, 5 mM, 10 mM, 15 mM, and 20 mM) of picric acid for different soaking times (3 h, 6 h, and 9 h) and the data on agromorphological characteristics were recorded. Control and test samples were collected and compared for genomic chloroplast studies. The results confirmed the inhibitory effect of picric acid on days to emergence, completion of germination, and percent emergence. Seeds treated with a dose of 20 mM delayed seedling emergence (6.15) compared to other treatments. In addition, the differences between seeds primed for 3 h (6.07), and 6 h (5.89) were also highly significant. Similarly, the effects of 0 mM (7.52), 5 mM (8.26) and 10 mM (8.11) doses on germination time were not significant. Comparison of the mean values with respect to germination showed that picric acid led to a reduction in the percentage emergence of the oilseed rape seedlings. A significant increase in leaf size was observed in the Nifa Gold cultivar (10.27). On the other hand, the differences in leaf size between the cultivars Dur e Nifa (9.51) and Abasin-95 (9.20) were not significant. The inhibitory effect of picric acid on the number of leaves could be due to the fact that the meristematic cells are damaged by the mutagen, leading to a reduction in the number of leaves. The Nifa Gold cultivar showed the highest value for plant height (17.53), and the highest number of siliqua (14.69) compared to other genotypes. The number of siliqua confirms that Nifa Gold is best adapted to picric acid in contrast to the other genotypes. However, the differences between the Abasin-95 cultivar (0.068) and the Nifa Gold cultivar (0.062) in terms of seed weight were not significant. The dose of 15 mM (37.72) showed the highest moisture content, followed by 10 mM (37.08), 0 mM (33.87), 5 mM (33.11) and 20 mM (32.73). The chloroplast genome of plants grown from picric acid-treated seeds was mutated. Therefore, annotation of the genome was not possible. Numerous single nucleotide substitutions (187) were detected between the control and test samples. In addition, 43 additions/deletions were observed. The present study suggests that picric acid has a mutagenic effect, which is confirmed by numerous mutations in chloroplast samples. Subsequently, the doses have stimulating effects on plant height and seed weight. Furthermore, priming can improve the emergence and certain biological characteristics of B. napus. In the present study, all parameters were investigated and the significant response of the selected genotypes was confirmed.